2008
DOI: 10.1016/j.micres.2006.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity, structure and CMC relationships of alkanediyl α,ω-bis(dimethylammonium bromide) surfactants

Abstract: Some alpha,omega-alkanediyl bis-dimethylammonium bromide compounds (gemini surfactants) referred as "m-s-m" have been synthesized, purified and characterized by usual spectroscopic methods. These compounds have been screened for antibacterial activity against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. Their activity was compared. The compounds tested showed excellent in vitro antibacterial activity against Staphylococcus aureus ranging from 1.5 to 20 microg/ml and had variable activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 7 publications
2
58
0
1
Order By: Relevance
“…It was also observed that with an increase in alkyl chain length of the gemini surfactants, the compounds exhibit a stronger antimicrobial effect due to a more hydrophobic environment and a lower CMC. These findings agree well with the existing reports that if the alkyl chain of quaternary ammonium compounds is shorter, the greater will be the CMC [13,19,26]. As a consequence, the antimicrobial power of 12-2-12 and 12-4-12 proves to be much weaker than the 16-s-16 series [24].…”
Section: Antimicrobial Testsupporting
confidence: 92%
See 1 more Smart Citation
“…It was also observed that with an increase in alkyl chain length of the gemini surfactants, the compounds exhibit a stronger antimicrobial effect due to a more hydrophobic environment and a lower CMC. These findings agree well with the existing reports that if the alkyl chain of quaternary ammonium compounds is shorter, the greater will be the CMC [13,19,26]. As a consequence, the antimicrobial power of 12-2-12 and 12-4-12 proves to be much weaker than the 16-s-16 series [24].…”
Section: Antimicrobial Testsupporting
confidence: 92%
“…Such quaternary ammonium salts kill microorganisms by damaging cytoplasmic membrane of cell and affect the permeability properties of cells, different from antibiotics that inhibit certain reproductive enzymes. Thus, the antimicrobial action of cationic surfactants is based on their ability to disrupt the integral bacterial membrane by a combined hydrophobic and electrostatic adsorption phenomenon at the membrane-water interface to create disorganization [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The minimal inhibitory concentrations (MIC) of gemini surfactants in some cases are even three orders of magnitude lower in comparison to their single surfactants [11,12]. Many cationic surfactants have a low Three biodegradable gemini cationic surfactants were synthesized and namely: N,N 0 -bis(2-hydroxyethyl)-N,N 0 -dimethyl-N,N 0 -bis(2-(tetradecanoyloxy) ethyl)ethane-1,2-diaminium bromide; N,N 0 -bis(2-hydroxyethyl)-N,N 0 -dimethyl-N,N 0 -bis(2-(tetradecanoyloxy) ethyl) hexane-1,6-diaminium bromide and N,N 0 -bis(2-hydroxyethyl)-N,N 0 -dimethyl-N,N 0 -bis(2-(tetradecanoyloxy) ethyl)dodecane-1,12-diaminium bromide.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their unusual properties (such as high surface activity, much lower cmc, higher solubilization capacity, low Krafft temperature, good wetting, detergency and emulsifying properties), the geminis have been considered the next generation surfactants [1][2][3][4][5][6][7]. Cationic geminis, in particular, have been shown to possess high antifungal, antibacterial and antimicrobial activities [8][9][10][11] and have attracted considerable attention towards their interaction with biologically important ligands [12][13][14][15][16]. Surfactants interact with the membranes causing cell lysis.…”
Section: Introductionmentioning
confidence: 99%